2010
DOI: 10.1007/s00213-009-1769-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of cannabis on eye movement control in reading

Abstract: The results indicate that relatively subtle performance deficits on the level of basic oculomotor control scale up as task complexity and cognitive demands increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…Many recent studies additionally revealed rather long-lasting effects on basic oculomotor control, especially after chronic use. [12] Even so, it is still unknown to what extent these deficits play a role in everyday tasks that strongly rely on an efficient saccade system, such as reading.…”
Section: Effect Of Cannabis On Cognitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many recent studies additionally revealed rather long-lasting effects on basic oculomotor control, especially after chronic use. [12] Even so, it is still unknown to what extent these deficits play a role in everyday tasks that strongly rely on an efficient saccade system, such as reading.…”
Section: Effect Of Cannabis On Cognitionmentioning
confidence: 99%
“…[20] There may be relatively subtle performance deficits on the level of basic oculomotor control that scale up as task complexity and cognitive demands increase. [12] Cognitive dysfunction associated with long-term or heavy cannabis use is similar in many respects to the cognitive endophenotypes that have been proposed as vulnerability markers of schizophrenia. [2122] Some studies have reported complete recovery of impairments after 4 weeks of abstinence, whereas other studies describe persisting cognitive deficits, especially in the domains of attention, memory and executive functions[1923] or only partial recovery of cognitive impairments in abstinent users.…”
Section: Evidence For Dose Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…17 Bartholomew et al 18 caution however, that young people may often not even notice the memory losses. Further, it also impacts visual motor skills, 18,19 general cognition and thinking processes 20 and can induce psychotic symptoms such as hallucinations and delusions, again, much like what is found in individuals with schizophrenia. 17 Paradoxically, cannabis is the most commonly used drug in individuals who suffer with schizophrenia.…”
Section: Cognitionmentioning
confidence: 87%
“…Eighty sentences taken from the work of Huestegge et al (2010) were presented one by one. Text was presented in regular Arial font size 16 pt corresponding to 0.24°at the given viewing distance of 60 cm.…”
Section: Methodsmentioning
confidence: 99%